How to cheer up Dad - Koehler, Fred (Dial Books for Young Readers, an imprint of Penguin Group (USA) LLC, 2014)
"A young elephant sees his dad is in a bad mood and tries to cheer him up, not realizing his own mischief caused the bad mood in the first place"--